Effects of isolated compound from Sonneratia caseolaris leaf: a validation of traditional utilization by melanin biosynthesis and antioxidant assays - Enos Tangke Arung, Harlinda Kuspradini, Irawan Wijaya Kusuma, Tran Hai Bang, Shuntaro Yamashita, Yoshinori Katakura, Kuniyoshi Shimizu (Journal of Applied Pharmaceutical Science, 2015)
In continuing to search new materials for skin whitening agent from natural resources, we have focused on plants used by Dayak tribe (native people in East Kalimantan, Indonesia) for skin care treatment. The ethanol extract of the leaves of Sonneratia caseolaris showed anti-melanogenesis activity in melanin biosynthesis assays using B16 melanoma cells. By activity-guided fractionation, luteolin-7-O-ß-glucoside (compound 1) was isolated as an active compound. In melanin formation inhibition assay, luteolin-7-O-ß-glucoside showed the inhibitory activity in a dose-dependent manner and reach 44% of inhibition at 223.2 μM with 92% of cells viability. The compound also showed potent anti-oxidative stress ability with a significant intracellular H2O2-scavenging activity in HaCaT cells. These results showed a validation of traditional use for skin care treatment by Dayak tribe in East Kalimantan.
Keywords: Sonneratia caseolaris,melanin biosynthesis,H2O2-scavenging,B16 melanoma cells